Penerapan Media Bermain Sunduuqus Sirri (Kotak Rahasia) pada Pembelajaran Kosakata Bahasa Arab Kelas V F Madrasah Ibtidaiyah Negeri 2 Sukoharjo Program Khusus Tahfidzul Qur’an - Annisa Nur Aisyah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2021)
This research is motivated by students' difficulties in vocabulary acquisition in Arabic language learning, which are influenced by the availability and utilization of learning media. These difficulties are not solely the students' fault but also stem from teachers who tend to use monotonous teaching methods without the aid of instructional tools or innovative approaches. The aim of this study is to understand the learning process involving the use of the Sunduuqus Sirri (secret box) game-based media at MIN 2 PKTQ Sukoharjo and to explore how this media is applied in the process of teaching Arabic vocabulary. This type of research is Classroom Action Research (CAR) conducted individually. The participants were 19 fifth-grade F students at MIN 2 PKTQ Sukoharjo. The instruments used to collect data included observation sheets, interviews, and documentation. The results of this study show that the use of the media led to improvements in the Arabic vocabulary learning process, as indicated by more active, enthusiastic, and enjoyable teaching and learning activities. The advantages of using this media include students gaining new knowledge about an example of learning media, increased student interest in the new media, and higher student engagement during lessons. However, a noted drawback is that some students were still not motivated by the new learning method.